(untitled) (Research, Society and Development, 2022)
The study was with the objective of determining the attractiveness and palatability of inclusion levels of hydrolyzed feather protein in diets for juvenile tambacu (Colossoma macropomum × Piaractus mesopotamicus). Six diets were formulated, according to the nutritional requirements of the species: positive control without feather hydrolysate (FPH0), 1% feather protein hydrolysate (FPH1), 2% feather protein hydrolysate (FPH2), 3% feather protein hydrolysate (FPH3), 4% feather protein hydrolysate (FPH4), and 5% feather protein hydrolysate (FPH5). For the test, 12 fingerlings with an average weight of 9.82 ± 0.74 g, distributed in 12 aquariums with volume of 20 liters and fed twice a day, at 10 am and 3 pm, with a previous selection of the diets offered, for a period of six days. In each feeding, 20 pellets were offered, and the events were filmed for three minutes, during which the following behaviors were observed: capture time of the first pellet (seconds), rejection of the pellet after capture, approach without capture, and pellets consumed, and later the palatability index was calculated, according to the equation of Kasumyan and Morsi (1996). The analyzes showed that all diets containing feather protein hydrolysate had a positive palatability index, in which they provided an increase in feed consumption in relation to the diet containing fishmeal. The FPH5 diet had the best palatability index (11.42%). Therefore, feather protein hydrolysate can be used in tambacu diets without altering palatability and feeding behavior.